Teaching music creatively - Burnard, Pamela; Murphy, Regina (Learning to teach in the primary school series, 2017)
Offering a brand new approach to teaching music in the primary classroom, this book provides training and qualified teachers with a comprehensive understanding of how to effectively deliver a creative music curriculum. Exploring research-informed teaching ideas, diverse practices and approaches to music teaching, the authors offer well-tested strategies for developing children's musical creativity, knowledge, skills, and understanding